IL MERCATO CERAMICO A REGIUM LEPIDI (AEMILIA) DAL PERIODO REPUBBLICANO AL TARDO ANTICO: PRODOTTI REGIONALI E IMPORTAZIONI - Biondani, Federico (Rei Cretariae Romanae Fautorum Acta, 2022)
Regium Lepidi is a small town in the VIII Regio (Aemilia) along the via Aemilia, probably founded in 175 BC. The aim of this study is to understand what pottery documentation can tell us about the trading relationships of this town from the Late Republic to Late Antiquity. - Republican age (2nd-end of 1st century BC): fine pottery, imported or local, suggests close relationships with Central Italy (black gloss ware, thin-walled ware, many types of common ware). Instead, coarse ware still shows types and decorations of pre-Roman tradition. - Early Empire: fine products are imported from Central Italy (Terra Sigillata Italica) and from the Eastern Mediterranean area (e.g. Eastern Sigillata B), but other pottery is mostly local or regional (Terra Sigillata padana, thin-walled ware, common ware). - Middle and Late Empire: documentation becomes scarce. Pottery is still mostly of local/regional production, but there are also fine imported products from the Adriatic area and from North Africa.